Dental Students’ Knowledge of Oral Health for Persons with Special Needs: A Pilot Study - Fouad Salama; Bader Al-Balkhi; Faika Abdelmegid (The Scientific World Journal)
Objectives. The purpose of this pilot study was to assess the knowledge and awareness of dental students with respect to oral health care of the person with special health care needs (SHCN) and evaluate effectiveness of an education program on improving their knowledge. Method. An evaluation consisting of a questionnaire was answered before and immediately after a 30-minute educational presentation in the form of a DVD that includes a PowerPoint and a video of oral health care for individuals with SHCN. The questionnaire was based on the materials and information presented in the DVD and included 26 questions (true/false/I do not know). Results. The mean (±SD) score on the pretest was 10.85 (±5.20), which increased to 16.85 (±5.47) on the posttest. This difference was statistically significant (P<0.001). Forty percent of the students surveyed reported that they were very satisfied with the educational part of the presentation, while 50% were somewhat satisfied. Thirty percent of students expressed that the educational intervention used is very effective. Conclusions. Viewing the educational intervention was effective in informing the sophomore students and providing them with instructive basic information on person with SHCN. Dental colleges should increase students’ knowledge, training, and exposure to individuals with SHCN.